La charte européenne de la coopération en matière d’appui à la gouvernance locale : outil et questionnements pour les autorités territoriales - Gaëlle Dusepulchre (Développement Durable et Territoires)
This paper tackles the new focus of the European Union on local authorities as actors for development. In putting it in its context, namely the strategies which promote governance and decentralization, the purpose of this article is two-fold. On the one hand, it seeks to highlight the assets of this new interest. On the other, it attempts to draw out some of the questions still pending